Applications of unmanned aerial vehicles in Antarctic environmental research - Tovar-Sánchez, Antonio; Román, Alejandro; Roque, David; Navarro, Gabriel (Scientific Reports, 2021)
Antarctica plays a fundamental role in the Earth's climate, oceanic circulation and global ecosystem. It is a priority and a scientific challenge to understand its functioning and responses under different scenarios of global warming. However, extreme environmental conditions, seasonality and isolation hampers the efforts to achieve a comprehensive understanding of the physical, biological, chemical and geological processes taking place in Antarctica. Here we present unmanned aerial vehicles (UAVs) as feasible, rapid and accurate tools for environmental and wildlife research in Antarctica. UAV surveys were carried out on Deception Island (South Shetland Islands) using visible, multispectral and thermal sensors, and a water sampling device to develop precise thematic ecological maps, detect anomalous thermal zones, identify and census wildlife, build 3D images of geometrically complex geological formations, and sample dissolved chemicals (< 0.22 µm) waters from inaccessible or protected areas. This research has been funded by the Spanish Government projects PiMetAn (ref. RTI2018-098048-B-I00), EQC2018-004275-P and EQC2019-005721. A. Román is supported by the Spanish FPU Grant (Ref: FPU19/04557). This research is part of the POLARCSIC research initiatives. Peer reviewed